MODEL- MODEL PEMBELAJARAN TEMATIK PERSPEKTIF PENDEKATAN SAINTIFIK - Asyahidah Alqurni; Riski Putri Nur Fadilah; Ismy Fatmawati; Siti Zikna Al Haiati; Imron Fauzi (STAI Ma'had Aly Al-Hikam Malang, 2023)
Often educators use a confessional approach or teacher-centered learning, resulting in many students being less effective and active in understanding thematic learning. As an educator, he should make a learning innovation that involves students in the learning process, namely by applying a scientific approach that is not only centered on the teacher but students are also involved in learning, so as to maximize learning objectives. The purpose of the study was to determine the application of scientific approach strategies to thematic learning. The method used in the preparation of the journal is library research by collecting various references in the form of books, journals. The results of this study explain the influence of the scientific approach applied to thematic learning such as asking, observing, reasoning, trying, and communicating. So that with this learning students become more active, think critically and learn systematically. By using a student-centered scientific approach, it will maximize the objectives of a learning process.